PanicRoom: a virtual reality-based Pavlovian fear conditioning paradigm - Lucifora, Chiara; Gangemi, Aldo; D’Italia, Giovanni; Culicetto, Laura; Ferraioli, Francesca; Grasso, Giorgio Mario; Vicario, Carmelo Mario (Frontiers in Psychology, 2024)
Pavlovian fear conditioning is an experimental paradigm used to study the acquisition and extinction of fear responses and various aspects of fear and anxiety. We developed a VR version of this paradigm to leverage the benefits of virtual reality, such as ecological validity, standardization, safety, and therapeutic applications. Our objective was to create an open-source, immersive environment for studying fear-related responses using the Unity Engine 3D and an Oculus Rift device.In this virtual environment, participants encountered a screaming monster at 100 dB approaching them as the fear-inducing stimulus (Unconditioned Stimulus or US). Our protocol includes three sessions: habituation, acquisition, and extinction, with two stimuli associated with different doors (blue vs. red). The blue door (CS+) is linked to the US, while the red door (CS-) is a control.We tested this VR paradigm on 84 young participants, recording their Skin Conductance Responses (SCR) and Fear Stimulus Ratings (FSR) on a 10-point Likert scale. The findings showed significantly higher SCR and FSR responses to CS+ compared to CS-during the acquisition phase and higher SCR and FSR for CS+ compared to habituation and extinction sessions. These results support the protocol's reliability for studying fear and anxiety-related conditions.